Morphological Study of Surface Magnetic Minerals, Case Study of North Banjarmasin Settlement Areas - Sudarningsih Sudarningsih; Fahruddin Fahruddin; Tetti Novalina Manik; Dzikri Dzikri (Lambung Mangkurat University Press, 2024)
We have conducted research to identify the morphology of magnetic minerals from the land in the Banjarmasin regional settlement area. We used scanning electron microscopy and energy dispersive X-ray spectroscopy (SEM EDS) on the soil sample to look at the shape of its magnetic minerals. In nature, magnetic minerals can indicate the presence of heavy metals. The shape of a magnetic mineral can reveal its origin in either the litogenic or anthropogenic processes. There were mostly pseudo-single domain grains (3.29–10 m) and multidomain grains (> 10–134.69 m) in the study area. The multidomain grains came in the shapes of sperules, irregulars, angles, and prisms. These results indicate that in the residential land location there are magnetic mineral grains originating from litogenic and anthropogenic processes.